The Method of Express Measurement of Moisture of Bulk Material During Pneumo Transport Process in the Pharmaceutical Industry, Based on the Pockels Effect (Review) - V. G. Gulyaev; I. V. Gulyaev (Разработка и регистрация лекарственных средств, 2019)
Introduction. The article presents data on the development and implementation of a method for measuring the moisture content of bulk material during its pneumatic transport in pharmaceutical production. The method of measuring moisture is theoretically based on the physical Pockels effect. An analysis of the currently existing pharmacopoeial methods for monitoring the quantitative water content and methods of in-process control of the drying process is presented. The development of new methods and technical means that provide the necessary speed and accuracy of moisture measurement is an important task, especially in the pharmaceutical industry to control the residual moisture of the starting materials, intermediate products during their production and finished products.Text. Analysis of the theoretical assumptions for the method and technical systems for measuring the mass of bulk dielectric materials during their pneumatic conveying shows the ability to measure the moisture content of the bulk dielectric material transported by air through a pipeline in a new non-contact manner. The proposed method is based on one measurable parameter – the intensity of the light wave passing through the Pockels cell. A block diagram of the system developed by the authors for automated moisture measurement of bulk dielectric materials with an electrooptical Poсkels cell is presented. The article describes a method for measuring moisture, based on the Pockels effect, for bulk material during its pneumatic transport.Conclusion. The proposed method of measuring moisture is contactless, just technically feasible, has a high speed and measurement accuracy, since it is based on the Pockels effect. The method is universal for determining the moisture content of bulk dielectric materials in the process of their pneumatic transportation. The above advantages of this method suggest the possibility of its successful application in pharmaceutical production.